Spectrophotometric Estimation of Paracetamol in Bulk and Pharmaceutical Formulations - P. Nagendra (E-Journal of Chemistry)
A new, simple and sensitive spectrophotometric method for the determination of paracetamol has been developed. The proposed method is based on the reaction of paracetamol with iron(III) and a subsequent reaction with ferricyanide in an hydrochloric acid medium to yield Prussian bluish green coloured product with a miximum absorption at 715 nm. There were no interferences observed from the common excipients present in the formulations. The method is successfully employed for the determination of paracetamol in various pharmaceutical preparations and the results have been statistically compared with those obtained by the official method.